Contrucción de un canal abierto de transporte de agua para la Facultad de Ingeniería. - Andrade Morocho, Fernando Patricio (2011)
In the formation of the Industrial Engineer one of the fundamental disciplines, it is that of Unitary Operations, which exactly analyzes the liquids or gases already be in balance, or in movement, being the fluids of major interest in our area. A fluid, as consequence of having a mass and a speed, can transport a quantity of movement. In addition, by virtue of his temperature, it is capable of carrying an energy. Strictly speaking the convection it is the transport of energy for movement of the way.